A Geographical Information System for Fire Management by the Western Cape Nature Conservation Board - Ford, Francois York (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2006.